Extending apple cultivation to lesser cold areas - Parmar, Chiranjit (Indian Horticulture, 2019)
First attempt to cultivate apple in less cold areas was made in sixties by the Himachal Pradesh State Department of Horticulture by starting a project, â€œResearch on apples and pears under low altitudes conditionsâ€ at Fruit Research Station, Bagthan at 3500 ft. Here a big varietal trial comprising around 100 varieties including some very recent varieties like Vered, Naomi, Tamar etc from Israel were planted. Unfortunately, this project was prematurely abandoned after 10 years.